2017
DOI: 10.1038/s41598-017-09983-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of paclitaxel and cetuximab by nanodiamond enhances mitotic catastrophe and tumor inhibition

Abstract: The poor intracellular uptake and non-specific binding of anticancer drugs into cancer cells are the bottlenecks in cancer therapy. Nanocarrier platforms provide the opportunities to improve the drug efficacy. Here we show a carbon-based nanomaterial nanodiamond (ND) that carried paclitaxel (PTX), a microtubule inhibitor, and cetuximab (Cet), a specific monoclonal antibody against epidermal growth factor receptor (EGFR), inducing mitotic catastrophe and tumor inhibition in human colorectal cancer (CRC). ND-PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 59 publications
0
26
0
1
Order By: Relevance
“…Surprisingly, ND-PTX-Cet significantly decreased tumor size in the xenograft model of EGFR-expressing human CRC tumors in nude mice. This study suggests that the co-delivery of PTX and Cet by ND enhanced the effects of mitotic catastrophe and apoptosis in vitro and in vivo [ 134 ].…”
Section: Types Of Nps Used For Combination Therapymentioning
confidence: 99%
“…Surprisingly, ND-PTX-Cet significantly decreased tumor size in the xenograft model of EGFR-expressing human CRC tumors in nude mice. This study suggests that the co-delivery of PTX and Cet by ND enhanced the effects of mitotic catastrophe and apoptosis in vitro and in vivo [ 134 ].…”
Section: Types Of Nps Used For Combination Therapymentioning
confidence: 99%
“…PTX has demonstrated outstanding antitumor activity due to high-affinity binding to microtubules, stabilizing and enhancing tubulin polymerization, and as suppressors of spindle microtubule dynamics (Wang et al., 2016 ; Zhang et al., 2018 ). Subsequently, all those actions contribute to the suppression of cell mitosis, motility and intracellular transport, which lead ultimately to the apoptosis of carcinomas (Lin et al., 2017 ). Due to the above properties, PTX has frequently been employed as a model drug among a number of important chemotherapeutic agents in recent cancer research (Yuan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their major limitation is dose-dependent side effects such as myelosuppression, cardiotoxicity, and the development of acute myeloid leukemia [39] . Many reports have shown that the binding of anthracyclines to the nanodiamond carriers significantly reduced the effective dosage, resulting in lesser side effects [40][41][42][43][44] . The first reports describing transportation of doxorubicin by nanodiamonds used drug physisorption onto nanoparticles.…”
Section: Nanodiamonds As Drug Carriersmentioning
confidence: 99%